Emerging Infectious Diseases in Mongolia - John R. Ebright; Togoo Altantsetseg; Ravdan Oyungerel (Emerging Infectious Diseases, 2003)
Since 1990, Mongolia’s health system has been in transition. Impressive gains have been accomplished through a national immunization program, which was instituted in 1991. Nevertheless, the country continues to confront four major chronic infections: hepatitis B and C, brucellosis, tuberculosis, and sexually transmitted diseases (STDs). As of 2001, only two cases of HIV infections had been detected in Mongolia, but concern grows that the rate will increase along with the rising rates of STDs and increase in tourism. Other infectious diseases of importance in Mongolia include echinococcus, plague, tularemia, anthrax, foot-and-mouth, and rabies.